The stolen book of Evelyn Aubrey - Burdick, Serena (Park Row Books, 2022)
England, 1898. When Evelyn first married the famous novelist William Aubrey, she was dazzled by his brilliance. But their newlywed bliss is brief when William is gripped by writer's block, and he becomes jealous of Evelyn's writing talent. When he commits the ultimate betrayal, stealing a draft of her novel and passing it off as his own, Evelyn decides to write her way out of their unhappy marriage. California, 2006. Abigail always wondered about her father, his identity forever lost when her mother unexpectedly died. Or so Abigail thought, until she stumbled upon his photo and a message that her great-great-grandmother was the author Evelyn Aubrey, leading Abigail on a journey to England in search for answers. There, she learns of Evelyn's shocking disappearance and how London society believed she was murdered. But from what she uncovers about Evelyn, Abigail believes her brilliant great-great-grandmother had another plot up her sleeve.